2009
DOI: 10.1007/s00784-009-0331-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in lightness, chroma, and hue in the anterior teeth of quinquagenarians and septuagenarians

Abstract: The purpose of this study was to evaluate, for both genders and two elderly age groups, differences in lightness, chroma, and hue of pairs of natural anterior teeth, so that more accurate information on color would be available for the production of dentures with a natural appearance. The subjects in the younger group (YG) were 54 to 56 years of age, those in the older group 73 to 75 (N = 195, 48% women). Tooth color was measured using a spectrophotometer. Mixed models were calculated for each pair of teeth, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 13 publications
1
42
0
2
Order By: Relevance
“…Conversely, b* was found to be related to age, both in the middle third and cervical areas . Eiffler et al were another of this small number who found no significant differences in tooth color among the 50‐year‐old group and the 70‐year‐old one …”
Section: Discussionmentioning
confidence: 96%
“…Conversely, b* was found to be related to age, both in the middle third and cervical areas . Eiffler et al were another of this small number who found no significant differences in tooth color among the 50‐year‐old group and the 70‐year‐old one …”
Section: Discussionmentioning
confidence: 96%
“…Especially when making the tooth color selection in an anterior restoration, the dentist often determines a single color for the central and lateral incisors and canine teeth. As a result, the natural appearance cannot be created for these anterior teeth, due to the uniform color appearance …”
Section: Discussionmentioning
confidence: 99%
“…Hue, represented by coordinate h*, is the first dimension of color and is associated to a color's dominant wavelength. It marks the difference among color families and is measured on a continuous scale ranging from 0 to 360 degrees . Value, represented by coordinate L* , is determined by the amount of black and white and is linked to the concept of lightness/darkness.…”
Section: Introductionmentioning
confidence: 99%